Perkembangan Sejarah Madrasah Di Indonesia - sudarto, sudarto (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2017)
Madrasahs in Indonesia have a very old history of Indonesian age. At the beginning of Islam's entry into Indonesia, the preachers made contact with the community. After the Islamic community was formed the local community began to build mosques. There are also in some areas that use pre-existing places as places of worship. The place of worship is then developed into Islamic education which later developed into a madrasah. To find out further madrasah developments, the authors summarize Madrasah books: History and Development. To complete the deficiencies in the book the author takes additional material from the book History of Growth and Renewal of Islamic Education in Indonesia and book History of Islamic Education: Tracing the Trace of Education Era Rasulullah to Indonesia.